Uncertainty of outcome or strengths of teams: an economic analysis of attendance demand for international cricket - Sacheti, Abhinav; Gregory-Smith, Ian; Paton, David (Taylor & Francis, 2014)
A significant body of theoretical literature has argued that popular interest in sporting contests between teams is heavily influenced by how difficult it is to predict the result ex-ante. Empirical research has, however, been unable to reach a consensus on the magnitude of uncertainty of outcome on demand. In this article, we seek to resolve this impasse by distinguishing between uncertainty of outcome in the short run and uncertainty of outcome in the long run. We also show that it is important to control for the independent effect of absolute team strength when testing the uncertainty of outcome hypothesis. Using data on over 380 Test cricket matches played in England, Australia and New Zealand since 1980, we find that short-run uncertainty of outcome has a significant impact on attendance demand and that absolute team strength has better explanatory power for attendance demand than does long-run uncertainty of outcome. Our results suggest some policy implications for the management and organization of international cricket.